2011
DOI: 10.1145/2001269.2001291
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sources of ineffciency in general-purpose chips

Abstract: o C To b E r 2 0 1 1 | vo L . 5 4 | N o. 1 0 | c o m m u n i c at i o n s o f t he acm 85 abstractScaling the performance of a power limited processor requires decreasing the energy expended per instruction executed, since energy/op * op/second is power. To better understand what improvement in processor efficiency is possible, and what must be done to capture it, we quantify the sources of the performance and energy overheads of a 720p HD H.264 encoder running on a general-purpose fourprocessor CMP system. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…One recent study showed that ISEs could eliminate the energy and performance gaps between software and ASIC implementations of an H.264 encoding, while automating the architectural design and verification process [8]. We believe that our approach achieves principally similar results for matching one 128-element query.…”
Section: Ises and Floating-pointmentioning
confidence: 67%
See 1 more Smart Citation
“…One recent study showed that ISEs could eliminate the energy and performance gaps between software and ASIC implementations of an H.264 encoding, while automating the architectural design and verification process [8]. We believe that our approach achieves principally similar results for matching one 128-element query.…”
Section: Ises and Floating-pointmentioning
confidence: 67%
“…The SoC will include some amount of specialized hardware for common functions that are performance and/or energy critical, while all other applications run in software. Prior work has shown that application-specific processors with specialized instruction sets (ASIPs) can almost equal the energy efficiency of applicationspecific integrated circuits (ASICs) [8], without sacrificing general-purpose functionality to support other applications.…”
Section: Introductionmentioning
confidence: 99%
“…ASIPs allow adding new functionality to an extensible baseline ISA in the form of Instruction Set Extensions (ISEs), thereby combining flexibility of a general purpose CPU and performance of an ASIC. The key idea is to analyse the application domain and identify repetitive source code fragments that can be replaced by custom ISE instructions to reduce NCL-EEE-MSD-TR-2012-177, Newcastle University 1 A. Mokhov, A. Iliasov, D. Sokolov, M. Rykunov, A. Yakovlev, A. Romanovsky: Synthesis of Processor Instruction Sets from High-level ISA Specifications overheads associated with the instruction fetch cycle and storage of temporary values [22], as well as to enable additional optimisation opportunities in resource allocation, register binding, and port assignment [15] [34].…”
Section: Introductionmentioning
confidence: 99%
“…Reconfigurable ASIPs address this requirement by combining a static general purpose ISA with a reconfigurable fabric to introduce new functionality when it becomes needed [11] [12]. Reconfigurability and custom instructions also address the issue of energy efficiency (a major concern for the microelectronics industry, particularly in mobile and embedded domains) by power elasticity [38] and by moving computationally intensive algorithms from software to hardware [22][27].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that full-custom, application-specific design of on-chip hardware accelerators, can provide orders of magnitude improvements in both power and performance for a wide variety of application domains [55,154].…”
Section: Introductionmentioning
confidence: 99%